2007
DOI: 10.1890/06-0901
|View full text |Cite
|
Sign up to set email alerts
|

Headwater Riparian Forest-Floor Invertebrate Communities Associated With Alternative Forest Management Practices

Abstract: Headwater streams and their riparian zones are a common, yet poorly understood, component of Pacific Northwest, USA, landscapes. We describe the ecological importance of headwater stream riparian zones as habitat for forest-floor invertebrate communities and assess how alternative management strategies for riparian zones may impact these communities. We compared community composition of forest-floor invertebrates at increasing distances along trans-riparian (stream edge to upslope) transects in mature forests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…In addition to the increased biological diversity inherent in the juxtaposition of aquatic and terrestrial habitats (Crow et al, 2000;Sabo et al, 2005), riparian zones have been shown to be unique from adjacent upland forest. Differences in vegetative composition (Goebel et al, 2003;Hagan et al, 2006) and in use by invertebrates (Rykken et al, 2007b), amphibians (Pauley et al, 2000;Perkins and Hunter, 2006;Crawford and Semlitsch, 2007), birds (DeGraaf and Yamasaki, 2000;Bub et al, 2004) and mammals (DeGraaf and Yamasaki, 2000;Ford et al, 2006) have been reported. The unique habitat qualities of riparian zones have been ascribed, in part, to their microclimatic conditions (Brosofske et al, 1997;Moore et al, 2005;Olson et al, 2007;Rykken et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the increased biological diversity inherent in the juxtaposition of aquatic and terrestrial habitats (Crow et al, 2000;Sabo et al, 2005), riparian zones have been shown to be unique from adjacent upland forest. Differences in vegetative composition (Goebel et al, 2003;Hagan et al, 2006) and in use by invertebrates (Rykken et al, 2007b), amphibians (Pauley et al, 2000;Perkins and Hunter, 2006;Crawford and Semlitsch, 2007), birds (DeGraaf and Yamasaki, 2000;Bub et al, 2004) and mammals (DeGraaf and Yamasaki, 2000;Ford et al, 2006) have been reported. The unique habitat qualities of riparian zones have been ascribed, in part, to their microclimatic conditions (Brosofske et al, 1997;Moore et al, 2005;Olson et al, 2007;Rykken et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…However the bulk of evidence in support of this comes from studies in more arid western forests (e.g., forest-floor invertebrates [Rykken et al, 2007b], amphibians [Olson et al, 2007]), where cool, moist microclimatic conditions in riparian zones are strongly different from those in adjacent upland forest (Rykken et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Higher water quality in streams associated to watersheds in the Andean Range, covered extensively with native forests, have been mentioned as an explanation for higher trout abundance compared to that reported for the Coastal Range and the Central Depression (Soto et al, 2006). Studies in the Northern Hemisphere show that forests with riparian buffers, resulted in a different forest invertebrate and aquatic invertebrate communities (Kiffney et al, 2003;Rykken et al, 2007) than in areas without forested buffers. Trout prey on both terrestrial and aquatic invertebrate communities (Elliott, 1973;Klemetsen et al, 2003) and they are most likely dependent on the communities associated to second-growth forests.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have investigated the effects of riparian buffer width and morphologies to protect various aspects of the riparian community (see Lee et al, 2004;Olson et al, 2007), which depend on the function that the buffer is meant to serve (Rykken et al, 2007), as well as site-specific conditions. This study investigated the role of three riparian buffers on preserving the biodiversity and community structure of aquatic macroinvertebrate and fish assemblages in Minnesota streams.…”
Section: Discussionmentioning
confidence: 99%